Recorrência do carcinoma hepatocelular após transplante de fígado com o nível de alfa fetoproteína - Coutinho, Madalena Maria Silva (2021)
Hepatocellular carcinoma (HCC) is the most common primary liver cancer subtype, accounting for approximately 90% of all primary liver cancers, and is the fifth most common cancer in the world with an annual worldwide incidence of over one million cases. About 90-95% of tumors are associated with cirrhosis of the liver. In the study performed in the Hepatic transplantation center of Ceara, were evaluated the variables of 391 patients submitted tohepatic transplantation (TH) due to hepatocellular carcinoma (HCC), diagnosed in the pre-transplant stage between August 2003 and December 2018. In this period the center realized1636 liver transplantations (LT).The tumor was more frequent in men with an average age of 52 to 65 years, the majoritywere infected with the hepatitis C virus, and alcohol abuse is the second etiological factor. Fourgroups were stratified by AFP level: (G1: AFP<100ng/ml, G2-AFP: 100-399ng/ml, G3-AFP:400-1000ng/ml, G4-AFP>1000nh/ml). G4 had the highest recurrence rate, with the graft itselfbeing the most affected organ. When comparing AFP less than 100ng/ml (GI) and greater than100ng/ml (GII), the recurrence was 6.7% and 20.2%, respectively. Analyzing the recurrencepreditctor variables, it was observed that patients in GII had a 2.8 times greater chance ofrecurrence than GI, and the presence of vascular invasion and nodules larger than 5cm increasethe chance of recurrence by 8 and 5 times more respectively. Overall recurrence was 9.7%,occurring mainly between two and five years after LT (37.8%) and relapse-free survival after200 months was 92%. Comparing with patients that underwent the downstage procedure, thesurvival was similar. The degree of tumor differentiation was not related to the level of AFP.However, the microvascular invasion found in the explant was related to the level ofAFP and tumor recurrence. In conclusion, LT for HCC provides excellent long-term survival,and that HCC associated with AFP greater than 100ng/ml increases the chance of recurrence. Tumor size, larger diameter, and microvascular invasion are significant risk factors fo rdetermining recurrence when associated with high levels of AFP.